Determinant Factors of Port Concession Performance with the Mediating Role of Port Performance - Anung Trijoko Wasono; Lim Sanny; Olfebri Olfebri; Johny Malisan; Prasadja Ricardianto; Ridho Bramulya Ikshan; Novita Widyaningrum (Dinasti Publisher, 2026)
This study investigates the factors determining concession performance in port concession schemes by examining the mediating role of port performance. Using an explanatory research design, data were collected through structured questionnaires administered to 15 private port terminals. The proposed model incorporates Investment, Tariff, Throughput, and Human Resources as exogenous variables, Port Performance as a mediating variable, and Concession Performance as the endogenous variable. Structural Equation Modeling (SEM) was employed to analyze the relationships among constructs. The results indicate that tariffs have no significant direct or indirect effect on concession performance. Investment and human resources exhibit significant positive effects on both port performance and concession performance, while port performance itself strongly influences concession performance. Throughput shows a significant negative direct effect on concession performance but does not significantly affect port performance. These findings suggest that concession success is primarily driven by effective investment utilization and workforce capability rather than pricing mechanisms or cargo volume alone. This study contributes to port governance and concession literature by emphasizing the importance of performance-based operational transformation in achieving sustainable concession outcomes.